PERAN KEPALA SEKOLAH SEBAGAI ADMINISTRATOR DI SMP MUHAMMADIYAH 17 CIPUTAT - fatimah, fatimah; As’ad, As’ad (RESEARCH AND DEVELOPMENT JOURNAL OF EDUCATION, 2018)
The purpose of this research is to analyze how the role of principal as administrator in Muhammadiyah 17 Ciputat Junior High School. The research uses qualitative approach and the method used is case study. Sources of data from the research is the principal as key informant (main source) and all teachers in Muhammadiyah 17 Ciputat Junior High School. The data collection procedure is done by interview, participant observation, and document analysis related to this research object. The results of the research findings reveal that there are three quite effective roles that the principal performs as an administrator: (1) planning school work programs, (2) running school organizational functions and (3) teacher task coordination.